The contribution of growth and maturation in the functional capacity and skill performance of male adolescent handball players - Matthys, S. P. J.; Vaeyens, R.; Coelho e Silva, M. J.; Lenoir, M.; Philippaerts, R. (International Journal of Sports Medicine, 2012)
The present study determined to what extent the variance in performance might be explained by chronological age, biological maturation, training load and anthropometry in 168 Belgian male handball players aged 14 years: anthropometric, strength, speed and sport-specific skills were assessed. MANOVA tested the effect of chronological age and biological maturity, whereas MANCOVA was used to compare maturity groups controlling for chronological age and training load. In addition, canonical correlation analysis was used between age, maturity-offset and anthropometry, on one side, and performance and sport-specific skills, on the other side. Results revealed significant differences between early, on-time and late maturity groups for anthropometry (p<0.001), strength (p<0.001) and sprint 20-m (p<0.05) in favour of the early maturing players. The difference between the mean values of the extreme groups for height was 24.8 cm, for weight 33.2 kg and, for body fat 6.5%; for handgrip 20.2 kg, for 5-jump test 1.1 m and for 20-m sprint 0.20 s. Maturity status had no effect on sport-specific skills. Canonical correlations indicated that poorer scores in sport-specific skills were related to fatness and lack of training. In parallel, a substantial relationship was found between early maturity-offset, body size, strength and 20-m sprint.